Atti performativi e costituzione della corporeità nel pensiero di Judith Butler - Ponzio, Julia (Rivista Italiana di Filosofia del Linguaggio, 2019)
The focus of this text is the question of the relation between body and language in Judith Butler’s thought. I will show that Butler’s attempt of a “more radical” use of the question of constitution, is connected with her critic of the concept of sovereignty. In order to work on this connection Butler interprets the “locutionary” and the “illocutionary” speech acts as two alternative models of constitution. Starting from this distinction Butler disconnects the idea of constitution from the question of sovereignty and connects it with the idea of agency.